A Heterotopian Escape Space in Bursa: Kanalboyu Street - Ali Yiğit (Coğrafya Dergisi)
In this study, the development processes of Soğanlı, a suburb (a peripheral neigborhood) of the city of Bursa, and Kanalboyu Street, which is located between the Soğanlı, Çirişhane, and Çiftehavuzlar neighborhoods, were examined as a heterotopic place of escape, given that it corresponds to the concepts of heterotopia and escapism. In the first part of this article, the concept of heterotopia is examined; the heterotopia concepts of Michel Foucault and Henri Lefebvre and the third space mooted by Edward Soja and Kevin Hetherington’s “counter-hegemonic spaces” are evaluated along with the critical views of several authors, and halaza as an original Turkish concept is highlighted. In addition, by examining the meanings that Yi-Fu Tuan attributed to the concept of escapism, it is argued that Kanalboyu Street is a breathing space for those attempting to escape from the oppressive atmosphere of the surrounding neighborhoods. Kanalboyu Street, the subject of our research, was considered a heterotopic escape place and was chosen as a case study. In the second part, the process of Kanalboyu Street’s emergence, which is the subject of the research and was chosen as a sample for the heterotopic escape space, is examined. The process of being occupied by the suburb of Soğanlı, a village near Bursa City, and the current functional characteristics of Kanalboyu Street, which was formed by a stream passing through the village’s land are described. While preparing the study, a descriptive survey model, a qualitative research method were used. The research data were obtained through a review of the relevant literature, long-term field observations, interviews, and mapping. The conclusion states that opening up a wide street in the unplanned and irregularly developed areas of cities can significantly improve the lives of residents.